Global and China burden and trend prediction of thyroid cancer attributed to high BMI from 1990 to 2021 - Teng, Zhibo; Dong, Yangfan; Duan, Shaobin (Frontiers in Oncology, 2026)
BackgroundWith economic development and lifestyle changes, the prevalence of obesity has increased significantly. However, limited research has investigated the trends in the burden of thyroid cancer attributable to high BMI.MethodsThis study utilized data from the Global Burden of Disease (GBD 2021) study. Joinpoint regression analysis was used to compute the average annual percentage change (AAPC) in age-standardized disability-adjusted life year (DALY) rates (ASDR) and age-standardized mortality rates (ASMR). An age-period-cohort (APC) model was used to analyze the effects of age, period, and birth cohort on the burden of thyroid cancer attributable to high BMI. The ARIMA model was applied to predict the global and national disease burden from 2022 to 2031.ResultsIn 2021, the rates of change in DALY number, crude DALY rate, ASDR, death number, and crude death rate for thyroid cancer attributable to high BMI in China exceeded the corresponding global rates compared to 1990. From 1990 to 2021, the global burden of thyroid cancer attributable to high BMI was higher in women than in men, whereas in China, the burden was higher in men than in women from 2010 to 2021. The peak burden occurred in middle-aged populations, with the burden increasing with age. From 1990 to 2021, the ASDR and ASMR for thyroid cancer attributable to high BMI showed an upward trend globally and in China. Projections indicate that the burden will continue to rise from 2022 to 2031.ConclusionFrom 1990 to 2021, the ASDR and ASMR for thyroid cancer attributable to high BMI exhibited an increasing trend globally and in China. The burden was higher in women than in men globally, but in China, it was higher in men than in women from 2010 to 2021. The burden increased with age. Projections suggest that the burden of thyroid cancer attributable to high BMI will continue to rise from 2022 to 2031.